A simple method to evaluate adhesion strength between metal layer and carbon fiber surface in metal-coated carbon fibers. (1st April 2019) - Kim, Kwan-Woo; Kang, Seong-Hyun; Rhee, Kyong Yop; An, Kay-Hyeok; Kim, Byung-Joo
Abstract: In this study, we proposed a new method to measure accurate adhesion strength between metal layer and carbon fiber (CF) surfaces in metal-plated CFs by using modified interfacial shear strength (IFSS) method. Conventional method to evaluate IFSS of metal plated CF with polymer resin creates error results because of the additional force a raised from metal layer demolition. In order to obtain exact values of the adhesion strength, metal layers above and below the polymer drop was removed by a mild acid solution. Therefore, it was possible to measure exact values of IFSS with very small error (error reduced from 45% to 15%). By this technique we clearly observed the effects of surface treatment of CFs on the enhancement of interfacial adhesion strength with polar metal layers (From 24.14 MPa to 28.87 MPa) and the neat adhesion strength without additional irregular forces (1.13 MPa, 4% higher value) by the demolition of metal layers on CF surfaces. So, it can be said that the IFSS results of all previously reported metal-plated fibers might be measured overly high.